2011
DOI: 10.1128/jb.05711-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Localization of a Bacillus subtilis Sortase and Its Substrate and Use of This Sortase System To Covalently Anchor a Heterologous Protein to the B. subtilis Cell Wall for Surface Display

Abstract: Sortases catalyze the covalent anchoring of proteins to the cell surface on Gram-positive bacteria. Bioinformatic analysis suggests the presence of structural genes encoding sortases and their substrates in the Bacillus subtilis genome. In this study, a ␤-lactamase reporter was fused to the cell wall anchoring domain from a putative sortase substrate, YhcR. Covalent anchoring of this fusion protein to the cell wall was confirmed by using the eight-protease-deficient B. subtilis strain WB800 as the host. Inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…This conclusion is further supported by the observation that the signal appears to form a spiral around the outside of the cell (Fig. 5 c), resembling the distribution of a sortase-anchored protein observed in B. subtilis [ 70 ].
Fig.
…”
Section: Resultssupporting
confidence: 73%
“…This conclusion is further supported by the observation that the signal appears to form a spiral around the outside of the cell (Fig. 5 c), resembling the distribution of a sortase-anchored protein observed in B. subtilis [ 70 ].
Fig.
…”
Section: Resultssupporting
confidence: 73%
“…In silico analysis showed that pLS20 did not contain a sortase gene. The bacterial genomes of most bacilli contain two genes, yhcS and ywpE , encoding probably functional but nonessential sortases ( 31 , 32 ). Remarkably, the genome of B. subtilis strain 168 used in our studies contains a deletion affecting the first 81 to 82 codons of ywpE and its entire upstream gene.…”
Section: Resultsmentioning
confidence: 99%
“…The host cell used in this study was B. subtilis WB800 strain [ 21 ], which was a gift from Dr. Sui-Lam Wong, University of Calgary, Canada. It contains the deletion of eight extracellular proteases, including nprE , aprE , epr , bpr , mpr , nprB , Δvpr, and wprA [ 20 ].…”
Section: Methodsmentioning
confidence: 99%